The Effect of the Team Game Tournament Learning Model on the Science Learning Outcomes of Class VI Students at SD Negeri 47 Sungai Raya - Susilawati, Sri; Fatmawati, Risdiana Andika; Afryaningsih, Yunika (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research was motivated by the low learning outcomes of students in grade VI science subjects at SD Negeri 47 Sungai Raya. The purpose of this study is to improve science learning outcomes in grade VI students of SD Negeri 47 Sungai Raya. This research is a classroom action research applying a model developed by Suharsimi Arikunto. The research was carried out in two cycles, each cycle held two meetings. One cycle consists of four stages of activity, namely the planning stage, the implementation stage, the observation stage, and the reflection stage. The subjects of this study were grade VI students of SD Negeri 47 Sungai Raya, Sungai Raya District, Kubu Raya Regency, in science learning in the odd semester of the academic year, totaling 24 students. Data collection techniques use observation, learning outcomes tests and documentation. The research instrument used is an observation sheet of student activities in applying the team game tournament learning model. As for the learning outcomes of students using learning outcome test sheets, namely in the form of written tests (pre-test and pos-test). The results showed that the learning outcomes of students increased from cycle I to cycle II. In cycle I the learning outcomes of students were 66.66% and in cycle II it became 83.33%. Based on the results of the study, it can be concluded that the application of the team game tournament learning model can improve the learning outcomes of students in grade VI science learning at SD Negeri 47 Sungai Raya.